2010
DOI: 10.1007/s00405-010-1320-1
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular and taste disorders after bilateral cochlear implantation

Abstract: The objective of this study was to investigate the occurrence of vestibular receptor deficiency and taste disorders after bilateral cochlear implantation in postlingually deafened patients and to find out whether the risk for these complications is higher for the second implantation. In a retrospective cohort study, we examined 20 patients (11-58 years, mean age 41.5 years), implanted sequentially between 2000 and 2007 (mean period between cochlear implantation 32.9 ± 25 months). Pre- and postoperative vestibu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 22 publications
4
52
1
1
Order By: Relevance
“…They found that specific testing showed in one case (5%) a unilateral taste disorder after ipsilateral cochlear and that there is a higher risk for subjective vertigo after the second implantation. To increase patients' and medico legal safety in the procedure, the occurrence of unilateral and/or bilateral vestibular dysfunction and the potential risk of taste disorder should be included in the risk counseling before bilateral CI [16].…”
Section: Resultsmentioning
confidence: 99%
“…They found that specific testing showed in one case (5%) a unilateral taste disorder after ipsilateral cochlear and that there is a higher risk for subjective vertigo after the second implantation. To increase patients' and medico legal safety in the procedure, the occurrence of unilateral and/or bilateral vestibular dysfunction and the potential risk of taste disorder should be included in the risk counseling before bilateral CI [16].…”
Section: Resultsmentioning
confidence: 99%
“…The data of oVEMPs after CI have not been reported yet. The rate of postoperative hypofunction was reported to be 13-86% in cVEMP (Todt et al, 2008;Krause et al, 2009;Licameli et al, 2009;Melvin et al, 2009;Krause et al, 2010;Wagner et al, 2010). Jin et al (2006)reported a response rate change in children with severe sensorineural hearing loss: seven of 12 patients presented normal cVEMPs before CI, but all disappeared after CI.…”
Section: Discussionmentioning
confidence: 95%
“…Adunka et al (2004) carried out a histological evaluation of electrode insertions, and they reported that smooth implantations via the round window membrane contributed to vestibular protection and successful insertion. Wagner et al (2010) reported that, with the modified RWA, only 22.7% (5/22) of patients exhibited hypofunction of cVEMP postoperatively, and the impact was relatively mild. The authors suggested that this could be related to surgical procedures, and they emphasized the benefit of the modified round window approach and its minor impact on the labyrinth.…”
Section: Discussionmentioning
confidence: 97%
“…We prefer the first option as it may limit the risk of hearing loss due to the introduction of a foreign body in the perilymphatic space. This is illustrated by an increasing number of publications reporting deleterious effects of cochlear implantation on the vestibular function [18,19] (approximately 1 mm 2 ) may be a problem in the future. During an acute experiment, the electrode can be precisely maintained in place for a few minutes, manually.…”
Section: Discussionmentioning
confidence: 99%